2012
DOI: 10.1259/bjr/88405305
|View full text |Cite
|
Sign up to set email alerts
|

Radiological staging in patients with hilar cholangiocarcinoma: a systematic review and meta-analysis

Abstract: Diagnostic accuracy studies of CT, MRI, ultrasound or PET/CT for staging of hilar cholangiocarcinoma are sparse and have moderate methodological quality. Data primarily concern CT, which has an acceptable accuracy for assessment of ductal extent, portal vein and hepatic artery involvement, but low sensitivity for nodal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 25 publications
(31 reference statements)
0
109
0
8
Order By: Relevance
“…Thus, few surgical centers propose the routine en-bloc PVR ("notouch" technique) (7,20,22,(44)(45)(46), while most of the surgical teams recommend the selective use of the PVR (2,5,6,11,15,18,21,23,25,28, 29,43), only when the preoperative imaging or intraoperative exploration suspect portal vein invasion by the tumor (8), as in was the case in the present series. A recent systematic review and meta-analysis have shown that the sensitivity and specificity of a preoperative contrastenhanced computed tomography in detecting a portal vein invasion in a PHC patient are 89% and 92%, respectively (47).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, few surgical centers propose the routine en-bloc PVR ("notouch" technique) (7,20,22,(44)(45)(46), while most of the surgical teams recommend the selective use of the PVR (2,5,6,11,15,18,21,23,25,28, 29,43), only when the preoperative imaging or intraoperative exploration suspect portal vein invasion by the tumor (8), as in was the case in the present series. A recent systematic review and meta-analysis have shown that the sensitivity and specificity of a preoperative contrastenhanced computed tomography in detecting a portal vein invasion in a PHC patient are 89% and 92%, respectively (47).…”
Section: Discussionmentioning
confidence: 99%
“…1). 9 According to a recent meta-analysis, the accuracy of ductal involvement of MDCT was 86%, 11 while…”
Section: 김소연 수술 전 영상학적 평가mentioning
confidence: 99%
“…12 It showed 84% sensitivity and 93% specificity to detect hepatic arterial involvement. 11 The accuracy for detection of portal vein has been reported as 87%. 13 Regarding lymph node metastasis, the sensitivity was 61% and the specificity was 88%.…”
Section: 김소연 수술 전 영상학적 평가mentioning
confidence: 99%
“…The lesion is usually hypoenhancing and may show enhancement in the delayed phase( Figure 9); occasionally it can enhance in arterial phase [30] . Intraductal papillary lesions show single or multiple intraluminal polypoidal soft tissue which show contrast enhancement and distend the lumen of the MDCT has an accuracy of about 86% in assessment of ductal extent of HiCC [28] . The sensitivity and specificity of MDCT in evaluation of portal vein, hepatic artery and lymph node involvement are 89% and 92%, 84% and 93%, and 61% and 88%, respectively.…”
Section: A B Cmentioning
confidence: 99%